Implementasi Pengendalian Risiko K3 Berbasis HAZOP Terhadap Lingkungan Kerja Pada Industri Kerupuk Tradisional: (Studi Kasus UD Mamak Kito, Kecamatan Tuah Madani, Pekanbaru, Riau) - Ardeline, Mela; Fadlilah, Lilya Irsianti; Syahputra, Ramdhani (Universitas Muhammadiyah Kendari, 2026)
The traditional cracker industry is a small business that still relies on manual production processes. This condition causes workers to face various potential hazards that can affect the safety, health, and comfort of the work environment. This study aims to implement Occupational Safety and Health (K3) risk control based on the Hazard and Operability Study (HAZOP) method in the traditional cracker industry. The study was conducted at UD Mamak Kito, Tuah Madani District, Pekanbaru City, from May to June 2026. This study is a continuation of previous research, by utilizing initial data from hazard identification as a basis for formulating risk control measures. The method used is descriptive quantitative through field observations, interviews, identification of production flows, preparation of HAZOP worksheets, assessment of likelihood and consequences, and classification of risk levels using a risk matrix. The results of previous studies indicate that there are 22 potential risks in the skin cracker production process, consisting of 10 high risks, 6 medium risks, and 6 low risks. The most dominant risks are related to non-ergonomic work postures, heat exposure, hot oil splashes, slippery floors, the use of sharp tools, and low worker compliance in using personal protective equipment. Control implementation is carried out through adjusting work positions, providing rest breaks, using PPE, improving floor cleanliness, regulating air circulation, and educating workers about healthy and safe work behaviors. The results of this study indicate that the HAZOP method can be used as a systematic approach in identifying sources of hazards and can be the basis for implementing simple, targeted, and appropriate K3 risk control for small businesses.